The diversity of root nodule bacteria associated with indigenous Lotononis spp. as determined by sodium dodecyl-sulphate polyacrylamide gel electrophoresis and 16S rDNA sequencing - Steyn, P.L. (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2006.